2018
DOI: 10.1002/cbin.11057
|View full text |Cite
|
Sign up to set email alerts
|

Sex influences diaphragm muscle response in exercised mdx mice

Abstract: Physical exercise promotes increased muscle damage in the mdx mice, the experimental model of Duchenne muscular dystrophy. Studies suggest that the estrogen level in females makes them less susceptible to muscle injuries. The aim of this study was to characterize the diaphragm (DIA) muscle response to physical exercise in male and female mdx mice. The animals were divided into four groups: female sedentary mdx; male sedentary mdx; female mdx submitted to exercise; and male mdx mice submitted to exercise. Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
(82 reference statements)
0
2
1
Order By: Relevance
“…While estrogen deficiency did not affect skeletal muscle strength, fatigability, or recovery of strength after fatigue in both the diaphragm and anterior crural muscles of female mdx mice in this study, gender and age effects have been shown to impact skeletal muscle physiology of dystrophic mice [63,64]. For example, Hakim et al showed that maximal sP o of EDL muscle in 6 mo female mdx mice was greater than aged-matched male mdx mice [63].…”
Section: Discussioncontrasting
confidence: 55%
“…While estrogen deficiency did not affect skeletal muscle strength, fatigability, or recovery of strength after fatigue in both the diaphragm and anterior crural muscles of female mdx mice in this study, gender and age effects have been shown to impact skeletal muscle physiology of dystrophic mice [63,64]. For example, Hakim et al showed that maximal sP o of EDL muscle in 6 mo female mdx mice was greater than aged-matched male mdx mice [63].…”
Section: Discussioncontrasting
confidence: 55%
“…Elevated CK levels are identified after physical activity, surgery and seizures 65 . It has previously been shown that physical demand leads to an exacerbation of CK serum concentration in mdx mice 66,67 …”
Section: Discussionmentioning
confidence: 99%
“…65 It has previously been shown that physical demand leads to an exacerbation of CK serum concentration in mdx mice. 66,67 The absence of dystrophin causes damage to the sarcolemma, inducing massive infiltration of immune cells, chronic inflammation, necrosis, and severe muscle degeneration 68,69 after muscle degradation. As well as depletion of regenerative capacity, fibrotic tissue is observed in the dystrophic muscle.…”
Section: Discussionmentioning
confidence: 99%